Stereomicroscopic evaluation of sealing ability of four different root canal sealers: an in-vitro study - Sonam Sah; Panna Mangat; Ajay Kumar; Neha Sah; Ganiga Channaiah Shivakumar; Marco Di Blasio; Gabriele Cervino; Giuseppe Minervini (BMC, 2024)
Abstract Aim To compare and evaluate the sealing ability of four different commercially available sealers to provide seal against the dye penetration test using a stereomicroscope-an in-vitro study. Material/Method 80 extracted single rooted mandibular premolar with single canal were used in this study. The samples were divided in 4 groups (20 in each) based on sealer. Group I (Diaproseal), Group II (apexit Plus), Group III (MTA Fillapex) and Group IV (Bio-C). The samples were analyzed using a stereomicroscope and data analysis was done with one-way Anova And post hoc Tukey's test. Result The mean dye penetration score was 1.2400 ± 0.778 mm for Group I. 2.6000 ± 0.897 mm for Group II, 4.2000 ± 0.923 mm for Group III and 4.225 ± 2.055 mm for Group IV. One-way Anova analysis shows that intergroup comparison was statistically significant between the four groups. The post hoc Tukey's test reveals that the difference was statistically non-significant between group III and group IV. Conclusion It was concluded that between the four groups the Group I (Diaproseal) showed the least dye penetration followed by Group II (Apexit Pus), Group III (MTA Fillapex) and then Group IV (Bio-C), where there was no significant difference between the Group III (MTA Fillapex) and Group IV (Bio-C).